A study on relationship of unit trust performances towards the benchmark of KLSE CI and syariah index: a case of Public Mutual Berhad / Noorul Hidayah Mohamed - Mohamed, Noorul Hidayah (Faculty of Business and Management, 2007)
This study is about the relationship of unit trust performance towards the benchmark of KLSE CJ and Syariah Jndex. The Public Mutual Berhad has been chosen as the case of this study since it is the largest private unit trust company in Malaysia. This research is conducted from 1st April 1999 - 31st December 2006 unit trust market return based on Net Asset Value (NAV) and the Kuala Lumpur Composite Index (KLCI) and Kuala Lumpur Syariah Index (KLSI) market return, using monthly basis. The correlation between those performances is also discussed. The scope of this study is narrowed and focused on equity fund only that is the Public Index fund and Public IttikaI fund in term of the performance benchmark comparison. In this study Public Index fund (dependent variable) is influence by the KLCI and Public Ittikal fund (dependent variable) is influence by the KLSI. The methods use to measure the objectives of the study can be achieved by using the data collection method, regression analysis and simple linear regression. The regression analysis comprises of correlation coefficient, coefficient of determination, T-statistic and Durbin Watson. In overall conclusion, this research shows that the unit trust performance does have a relationship to determine and estimate the performance of unit trust alone. This is supported by the findings from the previous research of Grinblatt and Titman (1994) which shows that inferences about fund performance can be dramatically affected by the chosen benchmark.